The potential of heparin-induced extracorporeal LDL/fibrinogen precipitation (H.E.L.P.)-apheresis for patients with severe acute or chronic COVID-19 - Jaeger, Beate Roxane; Arron, Hayley Emma; Kalka-Moll, Wiltrud M.; Seidel, Dietrich (Frontiers in Cardiovascular Medicine, 2022)
Patients with Long COVID and Acute COVID should benefit from treatment with H.E.L.P. apheresis, which is in clinical use for 37 years. COVID-19 can cause a severe acute multi-organ illness and subsequently in many patients the chronic illness Long-COVID/PASC. The alveolar tissue and adjacent capillaries show inflammatory and procoagulatory activation with cell necrosis, thrombi, and massive fibrinoid deposits, including unsolvable microthrombi, which results in an obstructed gas exchange. H.E.L.P. apheresis solves these problems by helping the entire macro- and microcirculation extracorporeally. It uses unfractionated heparin, which binds the spike protein and thereby should remove the virus (debris). It dissolves the forming microthrombi without a bleeding risk. It removes large amounts of fibrinogen (coagulation protein), which immediately improves oxygen supply in the capillaries. Additionally, it removes the precursors of both the procoagulatory and the fibrinolytic cascade, thus deescalating the entire haemostaseological system. It increases myocardial, cerebral, and pulmonary blood flow rates, and coronary flow reserve, facilitating oxygen exchange in the capillaries, without bleeding risks. Another factor in COVID is the “cytokine storm” harming microcirculation in lungs and other organs. Intervention by H.E.L.P. apheresis could prevent the uncontrollable coagulation and inflammatory activity by removing cytokines such as interleukin (IL)-6, IL-8, and TNF-α, and reduces C-reactive Protein and eliminates endo- and ectotoxins, without touching protective IgM/IgG antibodies, leukocyte or platelet function. The therapy can be used safely in combination with antiviral drugs, antibiotics, anticoagulants, or antihypertensive drugs. Long-term clinical experience with H.E.L.P. apheresis shows it cannot inflict harm upon COVID-19 patients.